Phenomenological Study: Muslim Self-Control in Responding to Shopee's “Flash Sale” - R. Nia Marotina (Tasfiyah : Journal of Islamic Law and Sharia Economics, 2025)
The phenomenon of flash sales as a digital marketing strategy on e-commerce platforms such as Shopee has triggered an increase in impulsive purchasing behavior, especially among millennials and Generation Z. This study aims to understand how Muslim consumers respond to this phenomenon from the perspective of Islamic concepts and self-control. Using a qualitative phenomenological approach, this study explores the subjective experiences of Muslim consumers in dealing with flash sale promotions, as well as their reflections on Islamic ethical consumption values. The results show that features such as countdown timers and free shipping create a sense of urgency and a perception of scarcity, which trigger spontaneous purchasing decisions. In Islam, the concept of nafs (ammarah, lawwamah, muthmainnah) and the principles of muamalah are important foundations in shaping ethical and moderate consumption behavior. Although an understanding of Islamic values and the level of self-control among Muslims can suppress impulsive urges, the stimulus of flash sales still has a strong influence. These findings highlight the importance of educating Muslim consumers about consumption ethics, as well as the need for more ethical and transparent marketing practices from e-commerce players to align with the principles of justice and honesty in Islam.